Relational Semantics for the Paraconsistent and Paracomplete 4-valued Logic PŁ4 - Robles, Gemma; López, Sandra M.; Blanco, José M. (Logic and Logical Philosophy, 2022)
The paraconsistent and paracomplete 4-valued logic PŁ4 is originally interpreted with a two-valued Belnap-Dunn semantics. In the present paper, PŁ4 is endowed with both a ternary Routley-Meyer semantics and a binary Routley semantics together with their respective restriction to the 2 set-up cases.